1995
DOI: 10.1001/archsurg.1995.01430060087016
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tumor Establishment and Growth After Laparotomy vs Laparoscopy in a Murine Model

Abstract: Tumors were more easily established and grew more aggressively after laparotomy than after insufflation. These results, coupled with those that demonstrate an immune advantage to laparoscopy over laparotomy, suggest that the difference in observed tumor growth may be related to immune function. While much work remains to be done, we believe these data provide evidence of a previously undemonstrated benefit of laparoscopic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
138
1
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(157 citation statements)
references
References 27 publications
14
138
1
4
Order By: Relevance
“…Experimental data suggest that surgical trauma may be associated with increased tumour growth (21)(22)(23)(24)31). Various potential mechanisms have been identified demonstrating a correlation between surgical trauma and tumour growth (6,25,26,31).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data suggest that surgical trauma may be associated with increased tumour growth (21)(22)(23)(24)31). Various potential mechanisms have been identified demonstrating a correlation between surgical trauma and tumour growth (6,25,26,31).…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that surgical resection of tumors may paradoxically contribute to the development of cancer recurrences. Murine studies have shown those laparotomy and bowel resections are associated with increased tumor growth and establishment vs results in anesthesia control mice [3][4][5] . In humans, numerous case reports have noted increased tumor growth soon after surgery in patients with residual cancer [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopically assisted vaginal hysterectomy has become the preferred approach for cervical cancer treatment. Experimental studies have shown that laparoscopic surgery has a low impact on cancer growth (15)(16). Mounting evidence shows that cervical cancer recurrence and survival rates after laparoscopic surgery are comparable with those observed after laparotomy, despite the results of prospective randomized trials.…”
Section: Discussionmentioning
confidence: 99%